2017
DOI: 10.1039/c7ra06269a
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical sensor based on Co3O4 nanosheets for lead ions determination

Abstract: In this work, Co3O4 nanosheets were fabricated on indium tin oxide (ITO) substrates by developing a simple electrochemical deposition and annealing method for lead ions detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 35 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…In a recent study, further improvements in analytical performance for the determination of Pb 2+ ions in water were achieved through electrodeposition of Co 3 O 4 nanosheets directly onto the indium tin oxide (ITO) electrodes. 877 The resulting electrodes, using DPASV, were capable of detecting Pb 2+ in 1−100 μg L −1 concentration range with the LOD of 0.52 μg L −1 and high selectivity against Ca 2+ , Mg 2+ , Fe 2+ , Zn 2+ , and Mn 2+ ionic interferents. Lin and co-workers used ultrathin two-dimensional TiO 2 nanosheets doped with fluorine, in layered electrode architecture (TiO 2 /GCE) for the detection of Pb 2+ ions.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study, further improvements in analytical performance for the determination of Pb 2+ ions in water were achieved through electrodeposition of Co 3 O 4 nanosheets directly onto the indium tin oxide (ITO) electrodes. 877 The resulting electrodes, using DPASV, were capable of detecting Pb 2+ in 1−100 μg L −1 concentration range with the LOD of 0.52 μg L −1 and high selectivity against Ca 2+ , Mg 2+ , Fe 2+ , Zn 2+ , and Mn 2+ ionic interferents. Lin and co-workers used ultrathin two-dimensional TiO 2 nanosheets doped with fluorine, in layered electrode architecture (TiO 2 /GCE) for the detection of Pb 2+ ions.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 95%
“…High sensitivity of the fabricated sensor was attributed to the presence of a nanochannel in the structure of Co 3 O 4 that are readily accessible for the diffusion of Pb 2+ ions providing large available surface area for metal crystal growth. In a recent study, further improvements in analytical performance for the determination of Pb 2+ ions in water were achieved through electrodeposition of Co 3 O 4 nanosheets directly onto the indium tin oxide (ITO) electrodes . The resulting electrodes, using DPASV, were capable of detecting Pb 2+ in 1–100 μg L –1 concentration range with the LOD of 0.52 μg L –1 and high selectivity against Ca 2+ , Mg 2+ , Fe 2+ , Zn 2+ , and Mn 2+ ionic interferents.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…22 The material's valence state, the elemental composition, and the phase composition are confirmed by X-ray diffraction (XRD) patterns. Figure 2E 42,43 Additionally, the OH groups and water molecules at the interlayer of LDH show a broadband at around 3400 cm −1 . According to the above results, it can be concluded that Co 3 O 4 /MoCo/LDH is successfully formed.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…The surface modification is key in obtaining excellent performance in terms of sensitivity and specificity, although the significant additional costs, both in terms of added labour and final price of the device represent a limiting factor. Moreover, the short-term stability and the reproducibility of the preparation of modified electrodes has been highlighted recently as an important issue, which discourages further applications especially in industry [28][29][30]. Bare electrodes, without functionalization, represent an interesting alternative, in particular when high sensitivity is not required.…”
Section: Introductionmentioning
confidence: 99%